2010
DOI: 10.1007/s10792-010-9354-3
|View full text |Cite
|
Sign up to set email alerts
|

Recalcitrant fungal tunnel infection treated with intrastromal injection of voriconazole

Abstract: We are reporting a case of recalcitrant fungal tunnel infection treated with intrastromal injection of voriconazole. A 50-year-old woman underwent an uneventful phacoemulsification through a temporal corneal tunnel incision for age-related cataract in her right eye. One month post-surgery, she developed tunnel infection. Microbiological investigations revealed Aspergillus flavus as the offending pathogen. Despite intensive medical treatment, the corneal and anterior chamber infiltrate progressively enlarged. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…Similarly, Tu16 reported success with intrastromal voriconazole in cases of Alternaria infection, and Jain et al 18 reported good outcome in a case of fungal infection of the phacoemulsification site tunnel with intrastromal voriconazole. In our study, all infiltrates involved more than half the thickness of the stroma and were unresponsive to 4 weeks of topical natamycin and voriconazole, and about two-thirds of our patients responded to intrastromal voriconazole.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Tu16 reported success with intrastromal voriconazole in cases of Alternaria infection, and Jain et al 18 reported good outcome in a case of fungal infection of the phacoemulsification site tunnel with intrastromal voriconazole. In our study, all infiltrates involved more than half the thickness of the stroma and were unresponsive to 4 weeks of topical natamycin and voriconazole, and about two-thirds of our patients responded to intrastromal voriconazole.…”
Section: Discussionmentioning
confidence: 93%
“…Jain V, et al (22) concluded that topical therapy along with a judicious use of intrastromal administration of voriconazole may be of immense benefit in refractory fungal keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…So, intracorneal voriconazole was reported to be safe and effective in deep recalcitrant fungal keratitis in the studies of Namrata Sharma, et al (19) Gaurav Prakash, et al (20) Ganapathy Kalaiselvi, et al (21) Jain V, et al (22) and Singh PK, et al (23) Shen YC, et al (24) conducted a retrospective, consecutive case series of 10 patients to report the therapeutic efficacy of intracameral voriconazole in the treatment of fungal endophthalmitis resulting from keratitis and concluded that intracameral voriconazole may be an effective treatment for fungal endophthalmitis contiguously spreading from keratitis. Gupta et al (25) reported that intracameral Voriconazole injection to be a safe and effective treatment in intracameral extension following penetrating keratoplasty for fungal keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal agents used include voriconazole, [1][2][3] amphotericin B, 4,7,8 and nystatin and miconazole 7 against infections such as Alternaria, 4 Fusarium, and Aspergillus 5 and Candida glabrata. 6 Bacterial keratitis is primarily treated topically because high minimum inhibitory concentrations can be achieved in the corneal stroma with topical administration of antibacterial agents.…”
Section: Discussionmentioning
confidence: 99%
“…Intrastromal antifungal injection has been useful in severe recalcitrant fungal keratitis, particularly if surgery has been refused or is contraindicated. [1][2][3][4],A Because the pharmacokinetic profile of topical antibacterial agents in the cornea is better than that of antifungal agents, the need for intrastromal antibacterial agents is rare. A review of the current literature found 2 reports on the use of intrastromal antibacterial agents, 1 in animals 5 and the other in humans.…”
mentioning
confidence: 99%